Timing of Bisphosphonate Initiation After Fracture: What Does the Data Really Say? - David W. Barton MD; C. Taylor Smith MS; Amit S. Piple BS; Sterling A. Moskal BS; Jonathan J. Carmouche MD (Geriatric Orthopaedic Surgery & Rehabilitation, 2020)
Introduction: Osteoporosis is often not clinically recognized until after a fracture occurs. Individuals who have 1 fracture are at increased risk of future fractures. Prompt initiation of osteoporosis treatment following fracture is critical to reducing the rate of future fractures. Antiresorptives are the most widely used class of medications for the prevention and treatment of osteoporosis. Many providers are hesitant to initiate antiresorptives in the acute post-fracture period. Concerns include interference with bone remodeling necessary for successful fracture healing, which would cause increased rates of non-union, malunion, and refracture. While such concerns should not extend to anabolic medications, physicians may also hesitate to initiate anabolic osteoporosis therapies due to high cost and/or lack of familiarity. This article aims to briefly review the available data and present a digestible narrative summary to familiarize practicing orthopaedic surgeons with the essential details of the published research on this topic. Results: The results of 20 clinical studies and key pre-clinical studies related to the effect of anti-resorptive medications for osteoporosis on fracture healing are summarized in the body of this narrative review. Discussion & Conclusions: While few level I studies have examined the impact of timing of initiation of osteoporosis medications in the acute post-fracture period, the few that have been published do not support these concerns. Specifically, data from level I clinical trials indicate that initiating bisphosphonates as early as 2 weeks post-fracture does not increase rates of non-union or malunion. By reviewing the available data, we hope to give clinicians the confidence to initiate osteoporosis treatment promptly post-fracture.